Development of professional pedagogical skills through the teaching chemical experiment in the Chemistry Didactics subject - Amil Sellés, Yissel Pérez de Villa; Bastida Lugones , Lazara; Rodriguez Morales , Alina (Revista Minerva, 2020)
The training process for education professionals currently requires the development of professional pedagogical skills, allowing them not only to apply knowledge but also to act and transform their object of work. In this sense, the activity conducive in students to the development and formation of the personality of emotional motivational and instrumental cognitive traits, but its success depends on the way in which it is assimilated, since it is not enough for the student to know, he needs to know do, what is possible by developing professional pedagogical skills. This concept has been defined by Torres as those activities (which include actions and operations) that teachers develop to successfully fulfill their functions as a professional educator and on the other hand, Fleites, N. (1999) considers them as the domain of Psychic and practical pedagogical actions that rationally regulate the teacher’s training activity, based on the assimilated knowledge about education and teaching.